Identifikasi Jenis dan Analisa Vegetasi Tumbuhan Air di Danau Lutan Palangka Raya - Tania Serezova Augusta (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
This research was conducted in Lake Lutan waters, Tumbang Rungan village, Palangka Raya, Central Kalimantan in May 2014. This study aims to identify and vegetation analyze the water plants in Lake Lutan.